Clinical characteristics and prognosis of 28 cases of infant acute lymphoblastic leukemia - Shi, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To analyze the clinical characteristics and prognosis of patients with infant acute lymphoblastic leukemia (IALL). Methods: A retrospective cohort study.Clinical data, treatment and prognosis of 28 cases of IALL who have been treated at Beijing Children's Hospital, Capital Medical University and Baoding Children's Hospital from October 2013 to May 2023 were analyzed retrospectively. Based on the results of fluorescence in situ hybridization (FISH), all patients were divided into KMT2A gene rearrangement (KMT2A-R) positive group and KMT2A-R negative group. The prognosis of two groups were compared. Kaplan-Meier method and Log-Rank test were used to analyze the survival of the patients. Results: Among 28 cases of IALL, there were 10 males and 18 females, with the onset age of 10.9 (9.4,11.8) months. In terms of immune classification, 25 cases were B-ALL (89%), while the remaining 3 cases were T-ALL (11%). Most infant B-ALL showed pro-B lymphocyte phenotype (16/25,64%). A total of 22 cases (79%) obtained chromosome karyotype results, of which 7 were normal karyotypes, no complex karyotypes and 15 were abnormal karyotypes were found. Among abnormal karyotypes, there were 4 cases of t (9; 11), 2 cases of t (4; 11), 2 cases of t (11; 19), 1 case of t (1; 11) and 6 cases of other abnormal karyotypes. A total of 19 cases (68%) were positive for KMT2A-R detected by FISH. The KMT2A fusion gene was detected by real-time PCR in 16 cases (57%). A total of 24 patients completed standardized induction chemotherapy and were able to undergo efficacy evaluation, 23 cases (96%) achieved complete remission through induction chemotherapy, 4 cases (17%) died of relapse. The 5-year event free survival rate (EFS) was (46±13)%, and the 5-year overall survival rate (OS) was (73±10)%.The survival time was 31.3 (3.3, 62.5) months. There was no significant statistical difference in 5-year EFS ((46±14)% vs. (61±18)%) and 5-year OS ((64±13)% vs. (86±13)%) between the KMT2A-R positive group (15 cases) and the KMT2A-R negative group (9 cases) (χ2=1.88, 1.47, P=0.170, 0.224). Conclusions: Most IALL patients were accompanied by KMT2A-R. They had poor tolerance to traditional chemotherapy, the relapse rate during treatment was high and the prognosis was poor